2015
DOI: 10.1534/g3.114.015669
|View full text |Cite
|
Sign up to set email alerts
|

Exome Sequencing Identifies a Rare HSPG2 Variant Associated with Familial Idiopathic Scoliosis

Abstract: Idiopathic scoliosis occurs in 3% of individuals and has an unknown etiology. The objective of this study was to identify rare variants that contribute to the etiology of idiopathic scoliosis by using exome sequencing in a multigenerational family with idiopathic scoliosis. Exome sequencing was completed for three members of this multigenerational family with idiopathic scoliosis, resulting in the identification of a variant in the HSPG2 gene as a potential contributor to the phenotype. The HSPG2 gene was sequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 65 publications
2
41
0
Order By: Relevance
“…Two other common variants of interest have recently been found to be associated with IS, but have yet to be replicated (Table 2) [63, 68]. New methodologies such as exome-sequencing have made it possible to identify rare variants associated with idiopathic scoliosis [4749, 81]. The importance of these findings in the general idiopathic scoliosis population, however, remains to be seen.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two other common variants of interest have recently been found to be associated with IS, but have yet to be replicated (Table 2) [63, 68]. New methodologies such as exome-sequencing have made it possible to identify rare variants associated with idiopathic scoliosis [4749, 81]. The importance of these findings in the general idiopathic scoliosis population, however, remains to be seen.…”
Section: Resultsmentioning
confidence: 99%
“…Baschal et al [47] sequenced the exomes of three affected individuals in a multigenerational family with dominant Mendelian inheritance of IS. They identified a rare missense variant in HSPG2 , coding for an extracellular matrix protein, also known as perlecan.…”
Section: Summary Of Genetic Findings In Idiopathic Scoliosismentioning
confidence: 99%
“…32, 2q36.1, 8q12, 10q24.31, 17q25.3, and 19p13.3) that may involve genes affecting growth and musculoskeletal development [28]. For example, next-generation sequencing, genotyping, linkage analysis, GWAS and gene expression studies in tissues have identified 23 genes that are related to scoliosis [29][30][31][32][33][34]. These genes code for extracellular matrix proteins, collagen, bone formation, mineralization and metabolism, growth and sex hormones, and homeobox genes required for differentiation of skeletal elements and structural integrity of the vertebrae.…”
Section: Introductionmentioning
confidence: 99%
“…39 Rare variants in the HSPG2 gene are linked to cases of idiopathic scoliosis. 40 STRC has a pseudogene with high genomic and coding sequence homology making it very difficult to characterize by normal short read sequencing methods. 41 The PMS2 gene has multiple pseudogenes, making it difficult to reliably detect mutations or characterize by sequencing.…”
Section: Long Range Pcr Confirmationmentioning
confidence: 99%